Patrol Pocket - Taharuddin, Nur Syazwin Ilani (IRC, 2020)
Patrol Pocket is a guard tracking system where guards can scan respective places or checkpoints using their mobile phone implemented with Near-Field Communication (NFC) and the system will record the time and location after each scan according to the officer’s unique ID. Administration officer can get updates through web portal to check the attendance of the patrol officer and the condition of each place. The system can also allow officer to report if the condition of each places is out of ordinary and call directly to the operational room. Each officer can check their performance by how many checkpoints being patrolled by them. They can view their performance after every patrol session and can download data from their patrol summary.